Building a Culture of Excellence: How Principal Supervision Shapes Professional Teachers through Collaborative Leadership - Hosna, Rofiatul; Ismail, Ismail; Fauzi, Ahmad (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to analyze the role of collaborative leadership in shaping professional teachers through supervision activities in madrasahs. The approach used is qualitative with a case study design. Data were collected through interviews, observations, and documentation. Data analysis was carried out through several systematic stages to ensure the validity of the findings, namely data condensation, data presentation, verification, and concluding. The study results indicate that collaborative leadership applied in madrasahs encourages the creation of positive, cooperative relationships between leaders and teachers, optimizes teacher involvement in decision-making, and encourages innovation in learning. In addition, this study found that ongoing teacher development programs are essential to maintaining the quality of teaching. These findings contribute to the development of collaborative leadership theory in Islamic education. They can be used as a basis for policy to improve the effectiveness of academic supervision in madrasahs. The implications of this study indicate the importance of implementing collaborative leadership in madrasah management to improve the quality of education and teacher professionalism, as well as providing guidance for policymakers in designing more effective and inclusive supervision programs.